Aktualisasi Model Pembelajaran PjBL Pendekatan Saintifik untuk Meningkatkan Keterampilan Proses Sains Siswa - Harahap, Fitra Hayati; Himsar, Himsar (Institut Agama Islam Negeri Padangsidimpuan, 2024)
Education is the process of forming students' competencies as a whole and integrated between attitudes, knowledge and skills, the government programs nine years of compulsory education to achieve this. Era 4.0 and Society 5.0 are changing all lines of society's life dynamically, be it economic, socio-cultural, agricultural, even the world of education. Based on research by the Word Economic Forum (WEF) 2020 in Kahar et al (2021), there are 10 main abilities that are most in demand. What is needed to face the era of industrial revolution 4.0 and society 5.0 is being able to solve complex problems, thinking critically, creatively, having management skills, being able to coordinate with other people, emotional intelligence, being able to assess and make decisions, being service oriented, negotiating skills and cognitive flexibility. This is compatible with the PJBL in Madrasah Aliyah darul ikhlas Islamic Boarding padangsidimpuan learning model which has steps including: 1. learning through processes of searching for data and information about problems raised by the teacher. 2. Learners who foster a sense and attitude of personal and group responsibility among students. 3. Learning that focuses on results or projects. 4. Results or projects are evaluated. The approach that is relevant to the PJBL model is the scientific approach. The learning process is a learning process that is designed in such a way that students actively construct concepts, laws and principles through the stages of observing, formulating problems, proposing and formulating hypotheses, collecting data, analyzing data. and conclude it. The PJBL model based on a scientific approach forms students' science process skills, PJBL based on a scientific approach for science process skills requires knowledge, skills and attitudes competencies.